Molecular evaluation of developmental competence of oocytes collected in vivo from buffalo and bovine heifers during winter and summer - Ferreira, Roberta Machado; Macabelli, Carolina H.; de Carvalho, Nélcio Antônio Tonizza; Soares, Júlia Gleyci; Gimenes, Lindsay Unno [UNESP]; Ferraz, Márcio Leão; Watanabe, Yeda Fumie; Watanabe, Osnir; Rodrigues, Carlos Alberto; Vieira, Laís Mendes; Meirelles, Flávio Vieira; Baruselli, Pietro Sampaio; et al. (My University, 2013)
Buffaloes and bovines are polyestrous and seasonal or annual livestock, respectively, that show reduced fertility during heat stress. To investigate whether reduced fertility is related to oocyte competence in both species, immature oocytes from buffalo and bovine heifers were collected during winter and summer and subjected to molecular analyses. In each season, heifers of both species had their follicular wave emergence synchronized with a standard protocol (Ferreira et al., 2011). Before being subjected to ovum pick up (OPU), cutaneous (CT; °C) and rectal (RT; °C) temperatures and respiratory rate (RR; breaths/min) were measured. Oocytes' RNA was extracted to evaluate the expression of target genes related to mtDNA replication/transcription (PPARGC1A, TFAM and MTCO1), apoptosis (BAX and BCL2) and HS (HSP90AA1 and HSPA1AB). ACTB, HIST1H2AG and GAPDH were initially chosen as housekeeping genes. In buffaloes, CT (35.0±0.4 vs 23.8±0.5), RT (38.7±0.1 vs 38.0±0) and RR (21.3±1.2 vs 15.4±1.1) were higher during summer than winter. However, in bovine heifers, RT (38.7±0.1 vs 38.6±0.1) and RR (44.8±1.5 vs 40.6±1.5) were similar in both seasons, while CT (31.6 ±0.3 vs 30.2±0.3) was increased during summer. Reduced expression of ACTB, HIST1H2AG and GAPDH was evidenced during summer, disqualifying them as housekeeping genes. Similarly, the expression of all target genes was reduced during summer in oocytes of both species. In summary, physiological responses to heat stress seem to be more intense in buffalo than bovine heifers. However, in both species, negative effects of heat stress upon oocyte quality occur at the molecular level and affects genes related to several biological functions.
Keywords: Apoptosis; Bovine; Buffalo; Gene expression; Heat stress; Oocyte quality